INSTITUTIONAL FEATURES OF THE UKRAINIAN ENERGY MARKET: CHALLENGES FOR TRADERS - Андрусів, Уляна Ярославівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article explores the institutional features of the Ukrainian energy market and identifies key challenges for energy traders in the current environment. It analyzes the current state and development trends of the institutional environment in the electricity, natural gas, and petroleum products markets. The research identifies key institutional barriers and regulatory constraints affecting traders’ activities, including: regulatory uncertainty, price restrictions, liquidity problems, imperfect exchange mechanisms, limited access to infrastructure, and information asymmetry. The specifics of market mechanisms and instruments available to traders in different market segments are systematized. The study reveals that Ukraine’s energy market is characterized by a complex institutional structure undergoing active transformation in accordance with European legislation requirements. The main challenges for traders are identified as: managing regulatory risks, developing effective forecasting strategies, managing counterparty credit risks, optimizing logistics operations, digital transformation of business processes, and diversification of the energy portfolio. Based on the analysis, directions for improving the institutional support for energy traders’ activities are proposed, including harmonization of the regulatory environment with European practices, development of exchange mechanisms and financial instruments, improvement of information disclosure systems, modernization of infrastructure, and promotion of digital transformation. The research proves that overcoming the identified challenges requires a systematic approach to organizing traders’ work that takes into account the institutional features of the Ukrainian energy market and involves the use of innovative technologies and risk management methods. The necessity of further research on methodological approaches to risk management and analysis of the impact of digital technologies on the transformation of business models of energy traders in Ukraine is substantiated.